ISLAMIC THOUGHTS ON INTERFAITH MARRIAGE IN LOCAL AND GLOBAL CONTEXT - Lutfan Muntaqo (LP3M Universitas Sains Al Qur'an, 2020)
This paper discusses the ulama thoughts regarding interfaith marriages, especially between Muslims and non-Muslims. Interfaith marriage is a phenomenon that has occurred since the early days of Islam. Prophet Muhammad and some of his companions are including those who practiced it. In the early development of Islam, this issue was an important theme for discussion. Verses and hadiths related to inter-religious marriages come to the fore. Talking about inter-religious marriage is closely linked to the issue of ahl al-kitab/The People of the Book. The interpretation of this terms, ahl al-kitab, becomes a key to determine the law of interfaith marriages. This paper will discuss the various views of scholars related to the interpretation of the term ahl al-kitab and their views on inter-religious marriages in the local context (Indonesia) and globally.